Post-Covid-19 Tourism In Bali: The Economy And Eco-Tourism - Gde Deny LARASDIPUTRA; A.A. Ketut JAYAWARSA; Nyoman Ari Surya DARMAWAN (Indonesia Strategic Sustainability, 2022)
The Covid-19 pandemic has spread and spread globally no less than 218 countries have been exposed, including Indonesia. Tourism is one of the sectors most affected by the Covid-19 pandemic. This pandemic has forced the country to carry out social restrictions and prohibit tourist visits between regions and from abroad. The real impact that can be seen is that workers in this sector experience a decrease in income, for this reason it is necessary to know the condition of tourism after the pandemic in Bali. In this study using a narrative review method. The result is that the development of tourist villages has contributed to community empowerment as tourism actors. Tourism and culture is an activity of exchanging information and symbols contained in it, such as traditions, arts, food, and other identities contained in the place to be enjoyed by every tourist. The Bali Provincial Government issued a strategic policy in the form of Bali Governor Regulation Number 99 of 2018 concerning Marketing and Utilization of Agricultural Products, Fisheries and Local Bali Industries.